Review of Blois, JP (2018), Medio siglo de sociología en la Argentina. Ciencia, profesión y política (1957-2007), EUDEBA, Buenos Aires, 335 pp. - Lazarte, Lautaro (Serendipities. Journal for the Sociology and History of the Social Sciences, 2026)
Juan Pedro Blois's book, Medio siglo de sociología en la Argentina. Ciencia, profesión y política (1957-2007) (Half a century of Sociology in Argentina. Science, profession and politics, 1957-2007) shows the consolidation of the history of sociology as a productive research field in that country. Relying on the renewal of studies on the history of social sciences, using a varied set of materials (university syllabus; student publications; institutional documentation on schools, research centers and professional organizations; interviews; etc.) and assembling previous contributions -from the same author and other researchers- the book undertakes the complex task of composing the mosaic of the vicissitudes through which the discipline went through in the country over fifty years ago. This catalog of sources allows readers to better understand the eventful local history of the discipline characterized, at least until the definitive return of democracy (1983), by a series of violent disruptions that caused the loss of institutional archives and invaluable voices and testimonies.